Co-sputtered phase-change Ga-Sb-Te thin films - Kotrla, Magdaléna; Janíček, Petr; Gutwirth, Jan; Halenkovič, Tomáš; Přikryl, Jan; Šlang, Stanislav; Chevire, Francois; Nazabal, Virginie; Němec, Petr (ROYAL SOC CHEMISTRY, 2024)
Thin films with compositions equally distributed through GaSb-GaTe and GaSb-Te tie-lines were fabricated by radio-frequency magnetron co-sputtering. Several characterization techniques (scanning electron microscopy with energy-dispersive X-ray analysis, temperature dependent grazing incidence X-ray diffraction, Raman scattering spectroscopy, variable angle spectroscopic ellipsometry and sheet resistance temperature dependences) were employed to evaluate the properties of both as-deposited and annealed Ga-Sb-Te films. The change in the crystallization temperature influenced by composition variations is studied along with the change in the optical properties upon crystallization induced by annealing. The optical contrast between the annealed and amorphous states at a wavelength of 405 nm reaches a value of similar to 1.85 which is comparable with that in the case of commercially used Ge2Sb2Te5. All films showed a drop in temperature-dependent sheet resistance (similar to 4-7 orders of magnitude) except for Ga5Sb2Te3 and Ga5SbTe4. The results obtained from X-ray diffraction reveal Sb, GaSb, gallium antimony telluride together with Sb2Te3 and Te as possible phases which appear in the films after annealing. Additionally, Raman spectra revealed vibrational modes between Ga and Sb, vibrations of Sb-Sb bonds, vibrations of Te-Te and vibrations of Sb-Te. Changes between amorphous and crystalline phase of thin films with compositions equally distributed through GaSb-GaTe and GaSb-Te tie-lines fabricated by radio-frequency magnetron co-sputtering were studied.
Tenké vrstvy Ga-Sb-Te s fázovou změnou připravené magnetronovým naprašováním
Keywords: raman-scattering; crystallization kinetics; phase change memory; ramanův rozptyl; kinetika krystalizace; paměť s fázovou změnou